Neurological Adverse Events Associated With Immune Checkpoint Inhibitors Identified Through Disproportionality Analysis of the FDA Adverse Event Reporting System - Tao Chen; Kexin Shu; Hongyi Xiao; Yonghua Yuan; Fujun Zhang; Yu Liu (Cancer Medicine, 2026)
ABSTRACT Background Neurological immune‐related adverse events (N‐irAEs) from immune checkpoint inhibitors (ICIs) are rare but potentially fatal. This study aimed to characterize their real‐world profile to support early detection and management. Methods We analyzed ICI‐associated individual case safety reports (ICSRs) in the FDA Adverse Event Reporting System (FAERS) from April 2011 to June 2023. Disproportionality analyses used the reporting odds ratio (ROR) and the Bayesian confidence propagation neural network (BCPNN). Associations between serious N‐irAEs and sex or age group (< 60 vs. ≥ 60 years) were assessed using chi‐squared tests. We also evaluated the co‐occurrence of myasthenia gravis with myositis and/or myocarditis and its association with mortality. Results A total of 3486 ICSRs involving N‐irAEs were identified, with 550 cases reporting fatal outcomes. A total of 4139 N‐irAE signals were detected; among these, 2560 signals corresponded to the top 10 Preferred Terms (PTs) with the highest reporting frequencies. The median time from ICI initiation to the onset of N‐irAEs was 82 days (IQR: 29–219 days). Of the 4139 N‐irAE signals, 1925 (46.5%) were classified as serious adverse events; no statistically significant differences were observed in their distribution by sex ( χ 2 = 2.492, p = 0.114) or age ( χ 2 = 2.946, p = 0.086). A total of 461 cases of myasthenia gravis were identified, of which 219 (47.5%) were concomitant with myocarditis and/or myositis. Among the 137 fatal cases of myasthenia gravis, 70 (51.1%) were concomitant with myocarditis and/or myositis. Conclusion This study offers a comprehensive characterization of N‐irAEs, highlights the fatality risk when myasthenia gravis co‐occurs with myocarditis and/or myositis, and underscores the importance of early recognition, multi‐system evaluation, and timely intervention to improve patient safety and optimize the risk–benefit balance of immunotherapy.